Institutional Determinants of Economic Growth in ECOWAS Sub-Region - Ukwueze, Ezebuilo Romanus; Aguegboh, Ekene Stephen (International Journal of Economics and Financial Issues, 2018)
Following neoclassical growth model, people became deeply interested in the factors that lead to economic growth, characterized by diminishing marginal returns, exogenously determined technical progress and substitutability between the factors of production, namely capital and labour. The new or endogenous growth theory enunciated different sets of factors for economic growth as human capital and innovation capacity. New wave of empiricists with the use of cross-sectional and panel econometrics identified the determinants of economic growth with better precision and confidence. The study is aimed at finding the institutional determinants of economic growth in ECOWAS countries. The panel data analysis – using data collected form Quality of Governance (QoG), (1946–2012) - suggests that countries are heterogeneous, controls for heterogeneity and collinearity, from whose result shows that for all the countries studied, institutions matter for growth except for political stability. It is also evident from the results that the institutions matter for economic growth, while integration does not among ECOWAS Economies. Keywords: Corruption, Governance, Institutional Reforms, Growth per capita, Property rights JEL Classifications: D02; E02; O43